To solve this system of equations, we can use the method of substitution.
First, we can rearrange the first equation to solve for x:
-7x + 6y = -1
-7x = -1 - 6y
x = (1/7) + (6/7)y
Next, we can plug the expression for x into the second equation and solve for y:
-7((1/7) + (6/7)y) + 3y = -10
-1 - 6y + 3y = -10
-3y = -9
y = 3
Finally, we can plug the value of y back into the expression for x to find the solution:
x = (1/7) + (6/7)(3)
x = 1/7 + 18/7
x = 19/7
Therefore, the solution to the system of equations is x = 19/7 and y = 3.
-7x+6y=-1
-7x+3y=-10
1 answer